STUDI KARAKTERISTIK PELAKU PERJALANAN DALAM WILAYAH PELAYANAN TRAYEK MAMBORO – MANONDA DI KOTA PALU - Batti, Joy Fredi (Jurnal REKAYASA dan MANAJEMEN TRANSPORTASI, 2011)
Develepment of urban transport infrastructure such as bus stop and transit routes must considerthe arrangement of user characteristic within the service area. Public transport infrastructuremust be put in a city also depends on the characteristic of an urban public transport users.The purpose of this study was to determine characteristic of public transport users in its servicearea of Mamboro – Manonda in Palu City. Characteristic of users of public transport arecollected through questionnaires spread along the route and the service area. Characteristic ofpublic transport users surveyed include the type of work, the destination of the trip, time ofroutine and non-routine trips, types of vehicle used by traveler and purpose of the trip of publictransport users.The result of this study found that the type of work of public transport user, 34% arestudents/college students, 19% are housewives, 18% are civil servants. Based on routine travel,trips destinations are dominated by other trip destinations (35%). For non-routine travel, alsodominated by other trip destinations (51%). Time traveling to conduct activities for users of publictransport, category of routine travel occured at 06.00 – 09.00 (56%). Time traveling to conductactivities for users of public transport, category of routine travel,occurred at 06.00 - 009.00 (56%). Time of routine travel activity at home from 12.00 to 14.00 (44%).Characteristic of the traveling based on the mode that is used predominantly by the type ofpublic transportation (36%) and lowest percentage is the taxi mode (0.37%).